Current Review of Atrial Fibrillation Detected After Stroke - Valentinus Besin (Sumatera Medical Journal, 2022)
Patients with atrial fibrillation (AF) have a greater probability of a stroke event than patients without AF. As a result of developments in cardiac monitoring, the diagnosis of AF during an ischemic stroke or transient ischemic attack has improved these years. More cases of AF detected after stroke (AFDAS) are reported, which has implications for future risk of recurrent stroke and prevention. This article provides the current review of AFDAS's monitoring and brief management.